(untitled) (Scientific journal of the Fergana State University, 2026)
By analyzing the absorption of different types of silk in the range of 1400–800 cm-1 in the IR spectra, Gly-Gly at 1015 cm-1, Ala-Ala at 970 cm-1 and absorptions at 998 and 975 cm-1 constitute the Ala-Gly bonds determined For. Also, from the bending vibrations of the IR spectrum, -OH and stretching vibrations of the C-O-C group were visible. The literature was compared and analyzed.